METHODOLOGY FOR IMPROVING THE SCIENCE OF "NETWORK TECHNOLOGIES" IN HIGHER EDUCATION INSTITUTIONS (Conferencea, 2024)
The rapid evolution of network technologies necessitates a transformative approach to education in higher education institutions. This thesis presents a comprehensive methodology aimed at improving the teaching and understanding of network technologies, focusing on curriculum development, instructional strategies, and the integration of advanced technologies. By fostering a culture of continuous improvement and aligning educational practices with industry needs, this methodology seeks to enhance student learning outcomes and prepare graduates for successful careers in a dynamic field.